"It makes it more real.”: Teacher Candidate Perceptions of a Clinically-Rich Middle Grades Teacher Preparation Program - Shawn A. Faulkner; Michael DiCicco (Current Issues in Middle Level Education, 2025)
The persistent divide between theory and practice in teacher education has long been a subject of concern among researchers and scholars (Darling-Hammond, 2006; Zeichner, 2010). This paper explores teacher candidate perceptions of a clinically-rich (NASUP, 2021) middle grades teacher preparation program that has worked to create a “third space” (Zeichner, 2010) through a school-university partnership with a local middle school. Semi-structured interviews were conducted with teacher candidates (n=23) at the time of program completion. Findings suggest teacher candidates felt prepared and valued clinically-based activities and experiences. Teacher candidates suggest future improvements to the program should include more experiences tied to the school site. Implications and future directions are discussed.